(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT This article delves into Walter Scott's profound influence on the development of the historical novel genre in English literature. Examining Scott's groundbreaking works, including "Ivanhoe" and "Waverley," the article explores how Scott merged fiction with historical settings and characters to create compelling narratives that transported readers to different time periods. By analyzing Scott's techniques, thematic explorations, and cultural impact, this article highlights his role as a pioneer in establishing the historical novel as a respected and enduring literary genre. Furthermore, it investigates the ongoing significance of Scott's contributions to the evolution of historical fiction and his lasting legacy in the literary world.